Adsorption of zinc from aqueous solution using zeolite / Zaidatul Fatimah Ahmad - Ahmad, Zaidatul Fatimah (2009)
In this study, the adsorption behavior of natural zeolite for zinc ion has been studied in order to consider its application to purity in metal finishing wastewater. The batch method has been employed using metal concentrations in solution ranging from 50 to 200 mg/L and different amount of natural zeolite ranging from 0.5 to 2.0 g. The percentage adsorption was determined for the adsorption system as a function of initial concentration and amount of zeolite. From this study, it was found that the percentage adsorption of zinc decreases with the increase in initial concentration of sample solution and it increases with the increasing amount of zeolite being introduced. The highest percentage of zinc adsorption is 91.94 % at the concentration of 50 ppm using 2.0 gram of zeolite while, the lowest percentage of adsorption of zinc is 57.74 % at the concentration of 200 ppm using 0.5 gram of zeolite. In conclusion, natural zeolite holds the great potential to remove zinc from industrial wastewater.